A Literature Review on Effects of Positioning and Early Ambulation on Coronary Angiography Complication - Sulaiman, Sulaiman Abubakar; Zafar, Dr. Shahiduz (Clinical Medicine And Health Research Journal, 2023)
Introduction: The study was carried out to get a greater awareness of the impact of early ambulation and positioning on coronary angiography complications. And to build an evidence study on what other research said. Objectives: The objective of this study is to review the effect of changing position and early ambulation on coronary angiography complications. Methods: I used search engines were Identified 700 articles, I excluded 500, then screened total of 200 articles, 150 articles are not my concern, I included 36 articles in this research Result: According to the various research early ambulation and early position is safe after coronary angiography because it is effective way to minimize the risk of back pain and has no linkage in increasing risk of vascular complications like bleeding or hematoma.